(untitled) (Transport systems and technologies, 2018)
The article proved that one of the most important and comprehensive tests for the implementation of newly designed rolling stock is the research on its impact on the rail-way transport infrastructure (track and switch point). Resent researches on the impact of the newly designed rolling stock on the track were analytic investigated. The investi-gation results showed that the researches on interaction between newly designed rolling stock and existing track remain currently important. The aim of this research is to obtain experimental test results concerning the impact of passenger car 61-779 mounted on bogies 68-7115, 68-7115, Execution 01 on the track and switch point under various speeds. The experimental tests results of the referred rolling stock impact on a tangent track, a curved track with a radius of 419, 906, 1530 m and also within the limits of the switch point of type P65, denomination 1\11 are summarized. Research analysis proved that the above-mentioned passenger car complies with the actual regulatory require-ments on rolling stock.